Fluorinated amphiphiles control the insertion of α-hemolysin pores into lipid bilayers. - Raychaudhuri, P; Li, Q; Mason, A; Mikhailova, E; Heron, A; Bayley, H (2011)
The insertion of fully folded and assembled ion channels and pores into planar lipid bilayers for electrical recording has been facilitated by the use of conventional detergents at a final concentration below the critical micelle concentration (CMC). After the desired number of channels or pores (often one) has been incorporated into a bilayer, it is important to prevent further insertion events, which is often done by awkward techniques such as perfusion. Here, we show that the addition of single-chain fluorinated amphiphiles (F-amphiphiles) with zwitterionic, simple neutral, and neutral oligomeric headgroups at a concentration above the CMC prevents the further insertion of staphylococcal α-hemolysin pores, MspA pores, and Kcv potassium channels into lipid bilayers. We found the commercially available F(6)FC (fluorinated fos-choline with a C(6)F(13)C(2)H(4) chain) to be the least perturbing and most effective agent for this purpose. Bilayers are known to be resistant to F-amphiphiles, which in this case we suppose sequester the pores and channels within amphiphile aggregates. We suggest that F-amphiphiles might be useful in the fabrication of bilayer arrays for nanopore sensor devices and the rapid screening of membrane proteins.